The Star, 2 November 2009 - [author not identified] (Star Publications (Malaysia) Berhad, 2009)
The Thai Buddist Chetawan temple in Petaling Jaya recently welcomed a royal delegation for the Annual Kathina ceremony with all the pomp and splendour accorded of the King of Thailand